Drivers of integrated environmental innovation and impact on company competitiveness: evidence from 18 Chinese firms. (19th April 2011) - Liu, Xielin; Dai, Hongyi; Cheng, Peng
This paper examines the drivers of environmental innovation and their respective effects on company competitiveness based on 37 interviews of 18 Chinese firms. The sample innovations are mainly integrated environmental innovations represented by clean process innovations and green product innovations plus a few end-of-pipe technologies. Our study found that environmental innovation is driven by a mixture of factors of environmental regulation, cost pressure, competitive advantages and customer pressure. That would yield proof for the so-called Porter Hypothesis, which assumes that environmental regulation stimulates innovation and leads to 'win-win' opportunities where simultaneously pollution is reduced and competitiveness increased.